A review on educational styles and evaluating relationship between conflict and effectiveness - Amiri Dogahe, Hossein; Razmara Meydanghah, Hamideh (Opción, 2019)
This study is done to investigate the effect of conflict management styles on employee creativity and organizational effectiveness in educational environments via comparative qualitative research methods. As a result, the relationship between social skills and self-sacrifice styles, cooperation and avoidance is statistically significant at the level of 0.01. In conclusion, in the formulation, modification and implementation of the employee evaluation plan, the employee members’ views and suggestions should be used to help them understand what dimensions of their work and behavior are being evaluated.